Extending the Technology Acceptance Model for Accounting Information Systems: A Comparative Analysis of Urban and Rural Users in Indonesia - Mardi Ari; Muhamad Rodi (Journal of Information Systems and Technology Research, 2026)
The adoption of Accounting Information Systems (AIS) in Indonesia remains uneven between urban and rural areas, reflecting disparities in digital competence, social conditions, and infrastructural readiness. Addressing this gap, this study extends the Technology Acceptance Model (TAM) by incorporating digital literacy, trust, and social influence, while explicitly examining the moderating role of geographical context (urban versus rural). A quantitative survey method was employed, collecting data from 300 AIS users, comprising 150 respondents from urban areas and 150 from rural areas. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) and multi-group analysis. The research model positions digital literacy, trust, and social influence as antecedent variables; perceived ease of use and perceived usefulness as mediators; behavioral intention as an intervening variable; and actual system usage as the outcome variable. The findings indicate that behavioral intention is a strong predictor of actual AIS usage in both urban and rural contexts. However, significant contextual differences emerge: digital literacy and trust positively influence perceived usefulness in urban areas, while these relationships are not significant in rural settings. This result highlights the moderating role of geographical context in shaping AIS acceptance patterns. This study contributes theoretically by extending TAM through a contextualized urban–rural perspective and empirically demonstrating the heterogeneous effects of key antecedents across geographical settings. From a policy perspective, the findings suggest that strategies to promote AIS adoption should be context-sensitive, with greater emphasis on digital capability development and trust-building mechanisms in rural areas.